Mineralocorticoids modulate the expression of the β-3 subunit of the Na+, K+-ATPase in the renal collecting duct. Issue 5 (3rd September 2017) - Rojas, Macarena; Díaz, Pablo; León, Pablo; Gonzalez, Alexis A.; González, Magdalena; Barrientos, Víctor; Pestov, Nikolay B.; Alzamora, Rodrigo; Michea, Luis
ABSTRACT: Renal sodium reabsorption depends on the activity of the Na +, K + -ATPase α/β heterodimer. Four α (α1–4 ) and 3 β (β1–3 ) subunit isoforms have been described. It is accepted that renal tubule cells express α1 /β1 dimers. Aldosterone stimulates Na +, K + -ATPase activity and may modulate α1 /β1 expression. However, some studies suggest the presence of β3 in the kidney. We hypothesized that the β3 isoform of the Na +, K + -ATPase is expressed in tubular cells of the distal nephron, and modulated by mineralocorticoids. We found that β3 is highly expressed in collecting duct of rodents, and that mineralocorticoids decreased the expression of β3 . Thus, we describe a novel molecular mechanism of sodium pump modulation that may contribute to the effects of mineralocorticoids on sodium reabsorption.